Traditional opal mining practice in Ethiopia, challenges and its economic impact on rural households: the case of wollo opal mining [version 2; peer review: 1 approved, 2 approved with reservations] - Addise Zemelak Sisay; Tadesse Wudu Abate (F1000Research, 2025)
Background The discovery spurred further exploration, leading to the expansion of opal mining into neighboring districts. Numerous cooperative groups, composed of small-scale miners, traditionally explore, develop, and extract significant amounts of rough opal gemstones. This study tries to investigate the challenges and economic impacts of traditional opal mining practice in wollo province of Ethiopia. Methods The study used in this study is primary data collected from rural households, which are living in five districts of north wollo zone, in Amhara regional state. The data was collected using field observation, focus grouped discussion, interview, and questionnaire from sampled households. The study uses both descriptive and econometric methods of data analysis to achieve its objective. Results Among the challenges of traditional opal mining, primitive way of exploring and extraction, limited access to market and low institutional support in terms of training and finance are identified. The probit model reveals that, increased education, access to training, and access to credit positively influence the likelihood of engaging in opal mining. The ESR model shows that, the average treatment effect on the treated (ATT) indicates that participating in opal mining increases monthly income by 31,380 ETB, while the average treatment effect on the untreated (ATU) shows a potential income increase of 31,625 ETB for non-miners if they engaged in mining. Conclusion The study identifies three main categories of challenges faced by traditional opal miners: exploration and extraction issues, market limitations, and regulatory and institutional shortcomings. Exploration and extraction challenges include the lack of modern mining tools and knowledge, as well as difficult terrain, leading to inefficient and hazardous mining practices. Market-related challenges involve limited access to broader markets and lack of value addition, resulting in miners selling raw opals at significantly lower prices compared to polished ones.